VD_FINDINFO HC / 2013 / 389 vom 8. Mai 2013 - VD Tribunal cantonal (2013)
DIVORCE, AUTORITÉ PARENTALE, DROIT DE GARDE, RETRAIT DU DROIT DE GARDE | 133 al. 1 CC, 133 al. 2 CC, 133 al. 3 CC, 133 CC, 310 al. 1 CC, 310 CC